152k views
3 votes
2. If f(x) = x – 5 and g(x) = x2 + 3, find f[g(-2)].

User Byorn
by
5.2k points

2 Answers

4 votes

Answer:

= 2

Explanation:

# g(x) = x^2 + 3 hence g(-2) = (−2)2+3=4+3=7

and so f(g(-2)) = f(7) = 7 - 5 = 2

User Dscher
by
5.3k points
6 votes

Answer: 2

Explanation:

F(x)= X-5

G(x) =X2 +3

Find F(g(-2))

G(x)= x2 +3

G(x)=G(-2);

X= -2

Substitute for x in g equation

G(-2)= (-2)^2+3

=4+3

=7

Therefore G(-2)= 7

F(g(-2))= x-5

Substitute for g(-2)= 7

F(7) = 7-5

=2

User Drew Gaynor
by
5.7k points